2005
DOI: 10.1021/ie050539b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on the Thermal Degradation of a Polyol Ester Lubricant Using GPC

Abstract: The thermal degradation of a polyol ester lubricant used as the main component of textile fiber finishes at high temperature (i.e., 220 °C) has been studied to model the real-world degradation of finishes on fiber manufacturing equipment. Chemical and physical analyses were performed on the thermally stressed lubricants using a combined analytical technique to measure the progress of degradation in the lubricant. The effects of two commonly used antioxidants in the fiber industry and two secondary arylamine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…From these thermal results, although the antioxidant behavior of TP was important, the blending‐induced interpenetration network structure was also considered to play a positive role. In fact, the enhancement of the thermal stability of the polymer through the addition of an antioxidation agent was reported by Mousavi et al in the case of polyester (PET). According to the results of Mousavi et al, we concluded that the enhancement of the thermal stability of these PAN/TP blends (Figure ) occurred because the presence of TP in the PAN network eliminated the occurrence of free radicals.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…From these thermal results, although the antioxidant behavior of TP was important, the blending‐induced interpenetration network structure was also considered to play a positive role. In fact, the enhancement of the thermal stability of the polymer through the addition of an antioxidation agent was reported by Mousavi et al in the case of polyester (PET). According to the results of Mousavi et al, we concluded that the enhancement of the thermal stability of these PAN/TP blends (Figure ) occurred because the presence of TP in the PAN network eliminated the occurrence of free radicals.…”
Section: Resultsmentioning
confidence: 89%
“…In fact, the enhancement of the thermal stability of the polymer through the addition of an antioxidation agent was reported by Mousavi et al 34 in the case of polyester (PET). According to the results of Mousavi et al, 34 we concluded that the enhancement of the thermal stability of these PAN/TP blends ( Figure 5) In the cooling-process recorded DSC curves, all of prepared PAN/TP blends showed a unique peak, as shown in Figure 6; this obviously indicated that these two materials blended with good miscibility. As shown in Figure 6, the crystallization temperature (T c ) of these blends was found to shift from higher to lower, corresponding to the TP percentage increase but was always smaller than that of the pure PAN.…”
Section: Mechanical Properties Of the Pan/tp Blendsmentioning
confidence: 88%
See 1 more Smart Citation
“…The usual two‐stage degradation pattern in PMMA is appeared in BC and ABC, due to the presence of the side chain and the main chain degradation of the polymer molecules (Hirata, Kashiwagi, & Brown, ). Mousavi et al developed a thermally stable polyol ester lubricant by addition of antioxidant (Mousavi, Wang, Grant, Oxenham, & Hauser, ). The team advocated that the addition of antioxidant improves the thermal stability of the polymer by the reduction of the gaseous oxidation rate of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…1,6 However, the appropriate introduction of friction modifiers, antiwear agents, antioxidants, or multifunctional additives into the lubricating system can effectively resolve these problems troubling lubricants. [7][8][9] Friction modifiers and antiwear agents, substances that can lower the coefficient of friction and reduce wear of mechanical components, have been the hotspot of research for many years. [10][11][12][13][14] In general, they contain some active elements to assure the excellent friction-reduction and antiwear properties, for instance, sulphur, phosphorous, nitrogen, and so on.…”
Section: Introductionmentioning
confidence: 99%